Om at formindske Brandfaren ved Staldbygninger. Foredrag, d. 25de Februar 1880. - Klein, Aug. (Tidsskrift for Landøkonomi, 2018)
Om at formindske Brandfaren ved Staldbygninger. Foredrag, d. 25de Februar 1880.